RURAL DEVELOPMENT FROM RURAL WOMENS PERSPECTIVE - Sercin, Ali; Lungu Oana, Maria; Calomfr Metescu, Ana-Maria (Economics of Agriculture, 2011)
This paper aims the approach of agriculture labor fluctuations, the main activity of the Romanian rural area but in terms of rural development under the current economic crisis. The analysis highlights the importance of rural development from the perspective of rural women, encouraging rural areas partnerships.